2013
DOI: 10.4238/2013.december.13.5
|View full text |Cite
|
Sign up to set email alerts
|

Review Structure, function, and localization of aquaporins: their possible implications on gamete cryopreservation

Abstract: ABSTRACT. The discovery of water channels (aquaporins, AQPs) was a landmark event for the clarification of water transport through the plasma membrane. AQPs belong to a family of intrinsic membrane proteins that act as selective channels for water and for solutes such as glycerol and urea. AQPs were found in different tissues and organs, including male and female reproductive systems. In the swine female reproductive system, the AQPs were localized in the uterus, oviduct, and ovary, as well as in the granulosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 58 publications
(86 reference statements)
4
33
0
Order By: Relevance
“…Moreover, this AQP was present in the granulosa and theca cells of follicular wall throughout the period of development until ovulation. Thus, this finding implies a possible involvement of AQP4 in folliculogenesis in the hen ovary similarly as it was strongly suggested for AQPs in mammalian ovaries (Grzesiak et al, 2016;McConnell et al, 2002;Sales, Lobo, Carvalho, Moura, & Rodrigues, 2013;Skowronska, Mlotkowska, Eliszewski, Nielsen, & Skowronski, 2015;Starowicz et al, 2014;Sun et al, 2007Sun et al, , 2009). These results, obtained for the first time in birds, are consistent with those previously reported in the human (Thoroddsen et al, 2011) and bovine (Williams, 2012) ovary, and extend the number of avian tissues in which presence of AQP4 has been shown, that is, the brain-a main place of AQP4 presence, proventriculus, muscle, kidney, ureter and testis (Goren, Adorján, & Kálmán, 2006;Nishimura & Yang, 2013;Saito, Ikegami, & Shimada, 2005;Skowronski, Leska, Robak, & Nielsen, 2009;Sugiura, Aste, Fujii, Shimada, & Saito, 2008;Yoshimura et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, this AQP was present in the granulosa and theca cells of follicular wall throughout the period of development until ovulation. Thus, this finding implies a possible involvement of AQP4 in folliculogenesis in the hen ovary similarly as it was strongly suggested for AQPs in mammalian ovaries (Grzesiak et al, 2016;McConnell et al, 2002;Sales, Lobo, Carvalho, Moura, & Rodrigues, 2013;Skowronska, Mlotkowska, Eliszewski, Nielsen, & Skowronski, 2015;Starowicz et al, 2014;Sun et al, 2007Sun et al, , 2009). These results, obtained for the first time in birds, are consistent with those previously reported in the human (Thoroddsen et al, 2011) and bovine (Williams, 2012) ovary, and extend the number of avian tissues in which presence of AQP4 has been shown, that is, the brain-a main place of AQP4 presence, proventriculus, muscle, kidney, ureter and testis (Goren, Adorján, & Kálmán, 2006;Nishimura & Yang, 2013;Saito, Ikegami, & Shimada, 2005;Skowronski, Leska, Robak, & Nielsen, 2009;Sugiura, Aste, Fujii, Shimada, & Saito, 2008;Yoshimura et al, 2011).…”
Section: Discussionsupporting
confidence: 79%
“…The basic structural difference between orthodox AQPs and GLPs is their pore size. Whereas the diameter of the pore is of 2.8 Å in the case of orthodox AQPs, it measures 3.4 Å in that of GLPs (reviewed by Sales, Lobo, Carvalho, Moura, & Rodrigues, ).…”
Section: Aquaporins: Ubiquitous Proteins In Live Organismsmentioning
confidence: 99%
“…AQP-1 is the most commonly expressed isoform (Denker et al 1988) and its expression has been reported in kidneys, lungs, red blood cells, brain, and uterus. This subunit participates in H 2 O reabsorption and secretion across the secretory epithelia (Sales et al 2013). Uterine AQP-1 was found to be distributed in stromal vasculature and was up-regulated by estrogen (Li et al 1997).…”
Section: Introductionmentioning
confidence: 97%